Metallurgical failure analysis of various implant materials used in orthopedic applications - Aksakal, B.; Yildirim, Ö.S.; Gul, H. (My University, 2004)
Implants made of titanium alloy Ti6Al4V and 316L steel obtained from revision operations between 1993 and 2002 were examined. Focus was on failed implant materials removed from patients undergoing coxarthrosis and scoliosis revision operations. The failed materials were examined metallurgically through a scanning electron microscope (SEM). The type of implant materials, their survival time in the body, their chemical composition, and the reasons for failure were accounted for. Analysis of the results revealed that the main reasons for failure are corrosive attack, manufacturing defects, and nonstandard-caused failures.
Keywords: Composition; Corrosion; Defects; Fatigue of materials; Implants (surgical); Metallurgy; Orthopedics; Scanning electron microscopy; Steel; Strength of materials; Titanium alloys; Corrosive attack; Coxarthrosis; Metallurgical failure analysis; Scoliosis; Failure analysis